Adsorptive catalysis of hierarchical porous heteroatom-doped biomass: from recovered heavy metal to efficient pollutant decontamination. Issue 34 (16th August 2018) - Wang, Jing; Yang, Qingfeng; Yang, Weixia; Pei, Hanna; Zhang, Liang; Zhang, Tianshu; Hu, Na; Suo, Yourui; Wang, Jianlong
Abstract : Hierarchical porous heteroatom-doped biomass integrates enhanced selective adsorption for heavy metal recovery and reuse in catalytic pollutant decontamination. Abstract : Extraction of heavy metals from wastewater serves to meet the global challenges of toxic metal waste remediation and valuable metal recycling. Herein, by utilizing a cheap and abundant biowaste of defatted soybean residues as a N-rich biomass precursor, a heteroatom-doped macroporous carbon biosorbent (denoted CKS) was formed through a one-pot pyrolysis method in the presence of potassium oxalate (activating agent) and calcium sulfate (hard template). Increased surface polarity with high sulfur doping (10.73 at%) results in the as-prepared material having a strong affinity for heavy metals due to soft acid-soft base interactions, and the optimized CKS-800 (pyrolyzed at 800 °C) shows high selectivity toward Cu 2+ and Ni 2+ with high distribution coefficients (6.7 × 10 5 mL g −1 for Cu 2+ and 9.8 × 10 4 mL g −1 for Ni 2+ ). Detailed isotherm studies demonstrate the excellent adsorption capacities of CKS toward Cu 2+ (1366.67 mg g −1 ), Ni 2+ (1250.21 mg g −1 ) and Pb 2+ (619.23 mg g −1 ). Moreover, the prepared CKS–metals (CKS–M) after metal remediation display superior catalytic capability both for organic pollutant degradation with peroxymonosulfate as an oxidant and catalytic reduction of toxic Cr VI to nontoxic Cr III with formic acid as a reducing agent. The synergistic effects of crystalline carbon and heteroatom doping render the low-cost hierarchical CKS biomass an effective adsorptive catalysis material for efficient water remediation and sustainable utilization in homogeneous catalysis, which avoids further disposal and valorizes the metal complex itself in a "circular economy" model for multi-pollutant decontamination.